An exploration of digital marketing, financial literacy, and website empowerment for small enterprises in Melaya Village, Bali - Made Ayu Jayanti Prita Utami; I Putu Okta Priyana; I Wayan Eka Dian Rahmanu; Ni Nengah Lasmini; Ni Kadek Herna Lastari (Universitas Muhammadiyah Malang, 2024)
This study aimed to empower small businesses in Melaya village, Jembrana Regency, Bali, through a program focusing on website training, digital marketing strategies, financial education, and product enhancement. Initiated by Politeknik Negeri Bali's Business Department, the research engaged stakeholders through workshops covering website development, SEO, social media marketing, and financial literacy. Participants included small business owners, employees, and local government representatives, fostering a collaborative approach tailored to community needs. Beginning with an observational phase in June 2023, the program assessed local demand for digital marketing and financial management. Practical workshops facilitated by experts addressed these needs, alongside efforts to enhance local products such as ginger, coffee, perfume, and cricket farming. Politeknik Negeri Bali oversaw the development of a digital platform to promote these businesses, supported by hands-on activities. Evaluation methods included participant feedback and business performance assessments, revealing improvements in digital presence, product quality, and financial management. This initiative highlights its contribution to market reach, decision-making, and overall business sustainability in Melaya village. By bridging knowledge gaps and effectively utilizing digital tools, this program offers a replicable model for empowering local businesses, fostering sustainable growth and community development.